Pengembangan Buku Ajar Tematik Berbasis Cerita Jong Dobo dan Permainan Tradisional Kabupaten Sikka Kelas IV Sekolah Dasar - Desi Maria El Puang; Maria Angelina Fransiska Mbari; Marianus Yufrinalis; Adriana Alfrida (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2023)
Local wisdom is one of the closest elements to students' daily life, so cultural elements cannot be separated in designing a lesson in schools because it can foster students' love for the culture of their area. This study aims to determine the quality of material, local wisdom, and media design in thematic textbooks based on jong dobo stories and traditional games of Sikka Regency grade IV elementary school. This type of research uses development research with a 4-D development model. The target subjects are teachers and students of grade IV SDK Nita 1. The data collection instrument uses validation sheets and teacher and student response questionnaire sheets. The data analysis technique in this study is qualitative and quantitative descriptive analysis. The results of the validation of textbook eligibility by learning experts are 94.11% with excellent information and are worthy of testing in class. The validation results by local wisdom experts obtained a percentage of 98% eligibility with excellent information and very worthy of being tested in class. The validation results by design experts obtained a percentage of 88.75%, with excellent information and worth testing in class. The product trial results showed that student responses reached 98.54% with excellent information, and teacher responses obtained a percentage of 90.66% with excellent information. The thematic textbooks based on jong dobo stories and traditional games of Sikka Regency are excellent and very worthy of being used as a learning resource in the learning process in grade IV elementary schools.